Characteristics and seismogenic structure of the April 2024 Weishan (Yunnan, China) MS4.1 and MS4.3 double-earthquake sequence - Hei, Hetang; Zhang, Tianyu; Zhang, Yuan; Wang, Jun; Cha, Wenjian; Zi, Chengzhu; Gao, Qiong (Frontiers in Earth Science, 2025)
According to the China Earthquake Networks Center (CENC), two moderate earthquakes of MS 4.1 and MS 4.3 struck Weishan County, Yunnan Province, at 05:54:10 local time on 19 April 2024 and 13:05:16 local time on 24 April 2024, respectively, constituting a double-main-shock sequence. Using the double-difference relocation algorithm and Cut-and-Paste (CAP) waveform inversion, we precisely located 115 events (ML ≥ 0) and determined focal mechanisms for the two main shocks. Integrated with regional geological mapping, our results show: (1) The sequence trends NW–SE (∼8 km) with a subsidiary NE–SW lobe (∼4.5 km) and hypocentres concentrated at 3–11 km depth; both shocks exhibit normal faulting with a left-lateral strike-slip component; (2) Rupture was controlled by the NE–SW-striking Bianjiang Fault and the Jijie–Longjie anticline hinge, producing a downward-converging, cone-shaped seismic cloud; (3) Static Coulomb stress change (ΔCFF = +0.023 MPa) and magnitude parity confirm mutual triggering, consistent with a doublet rather than a foreshock-main-shock pair. Within the context of southward-migrating M ≥ 5 earthquakes in the Lanping–Simao terrane since 2013, the 2024 Weishan doublet highlights the reactivation of inherited fault-fold intersections driven by ongoing southeastward extrusion of Tibetan Plateau crust and provides a basis for future seismic-hazard assessment.